(untitled) (Journal of Dhaka Medical College, 2016)
Chronic Subdural Heamatoma (CSDH) is defined as collection of blood in the brains surface, subdural space between dura and arachnoid. It is one of the most common clinical entities in daily neurosurgical practice among the elders, several weeks after the head injury. CSDH doesnt always produce symptoms but when it does, it generally requires surgical treatment. The diagnosis and treatment are well established, but the cause of recurrence, complications and related factors are not completely understood. This study evaluated the clinical features, radiological findings and surgical results in a large series of patients treated at the Neurosurgery department of Dhaka Medical College Hospital. 300 consecutive patients (250 men and 50 women) age ranging from 30-85 years, GCS 5-15, volume of blood >25cc, symptomatic with CSDH were treated by one or two burr hole craniostomies. Haematoma cavity was irrigated with normal saline and closed system subdural drainage was continued for 1-2 days from January 2012 to December 2015. The clinical outcome was measure on 1st, 3rd, 5th and 7th POD using GCS scoring and GOS after 4 and 8 weeks of operations. Most patients 94%(282) had good recovery (GOS 5,4,3), 4%(12) showed no changes (GOS 2) and 2%(6) worsened (GOS 1). Recurrence of haematoma was recognized in 5%(15) patients 1-8 weeks after the first operation. 4%(12) patients suffered post operative complications of which 1.33%(4)patients were acute subdural haematoma caused by incomplete haemostasis of the scalp wound, 1.33%(4)patients were tension pneumocephalus and remaining due to hypertension, use of anticoagulants, poor general health and medical problems. Careful haemostasis and complete replacement of subdural haematoma with normal saline to prevent influx of air into the subdural space will further improve the surgical outcome for patients with CSDH. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 126-131